Treatment with chitin microparticles is protective against lung histopathology in a murine asthma model - AKKOÇ, TUNÇ (WILEY, 2006)
Chitin, a natural polysaccharide extracted from shrimp, is a potent T and B cell adjuvant when delivered in the form of chitin microparticles and can shift a polarized T-helper type 2 (Th2) immune response towards a Th1 response. We investigated the beneficial effects of the intranasal application of chitin microparticles in newborn mice before and after the establishment of a model of allergic asthma. Mice were grouped as asthma (A), primary prevention (PP), treatment (T), primary prevention+treatment (PPT) and control (C) groups. All mice except controls were sensitized with ovalbumin intraperitoneally and challenged intratracheally to establish the asthma model. Mice in the PP and PPT groups received chitin microparticles intranasally during the newborn period before sensitization. Mice in the PPT and T groups received intranasal chitin microparticles after challenge. Airway histopathology was evaluated in all groups. All of the airway histopathologic parameters of small and medium-sized airways of the T and PPT groups were significantly ameliorated when compared with the asthma model group. In the large airways, thicknesses of basement membrane, epithelium and subepithelial smooth muscle layers of the PPT group and basement membrane thicknesses of the T group were also significantly lower compared with the asthma model group. Comparison of the PP group with the asthma model group revealed significantly reduced goblet cell numbers and significantly reduced epithelial and basement membrane thicknesses in small and medium airways, in addition to significantly reduced basement membrane thicknesses in the medium-sized airways. Intranasal application of microgram quantities of chitin microparticles had a beneficial effect in preventing and treating histopathologic changes in the airways of asthmatic mice.
Keywords: airway histopathology; asthma; BALB/c; chitin microparticles; ACIDIC MAMMALIAN CHITINASE; HEAT-KILLED LISTERIA; T-CELL CYTOKINES; CPG OLIGODEOXYNUCLEOTIDES; ATOPIC ASTHMA; INFLAMMATION; MODULATION; RESPONSES; ADJUVANT; IMMUNITY